Tillämpad kulturanalys: Marknadsföring av ett humanistiskt samhällsperspektiv - Ehn, Billy; Nilsson, Bo (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
Since 2002 the Department of culture and media at the Umeå University runs a four years undergraduate programme of Cultural Analysis. Besides the conventional academic training in different interdisciplinary courses the students devote a lot of time practicing at the labour market. One central goal for the programme is that the students learn how to transform theoretical knowledge to practical use in various enterprises and organisations. Another goal is that they shall know how to market their acquired competence as cultural analysers — not precisely an ordinary task in the humanities. The tensions between theory and practice in this education programme certainly create some conflicts among the students, but contribute also to the development of a more conscious application of cultural analysis in the life outside the academy.